Síndrome metabólica em mulheres na pós-menopausa tratadas de câncer de mama - Nahás, Eliana Aguiar Petri [UNESP]; de Almeida, Bruno da Rosa [UNESP]; Buttros, Daniel de Araújo Brito [UNESP]; Vespoli, Heloísa Maria de Luca [UNESP]; Uemura, Gilberto [UNESP]; Nahas-Neto, Jorge [UNESP] (My University, 2012)
PURPOSE: To assess the occurrence of metabolic syndrome (MetS) in postmenopausal breast cancer survivors. METHODS: A total of 158 breast cancer survivors were included in this cross-sectional study. Eligibility criteria were: women with amenorrhea >12 months and age ≥45 years, treated for breast cancer and no metastasis for at least five years. Clinical history and anthropometric indicator data (body mass index (BMI), and waist circumference, (WC) were collected. Biochemical parameters, including total cholesterol, HDL, LDL, triglycerides (TG), glucose and C-reactive protein (CRP), were measured. MetS was diagnosed as the presence of at least three of the following diagnostic criteria: WC>88 cm, blood pressure≥130/85 mmHg, triglycerides≥150 mg/dl, HDL <50 mg/dL,and glucose≥100 mg/dL. The Student's t-test and χ 2 test were used for statistical analysis. RESULTS: The mean age of breast cancer survivors was 63.1±8.6 years, with a mean follow-up of 9.1±4.0 years. MetS was diagnosed in 48.1% (76/158) and the most prevalent diagnostic criterion was abdominal obesity (WC>88 cm), affecting 54.4% (86/158) of the women. The patients without MetS had a longer follow-up compared those with MetS (p<0.05). Regarding the current BMI, PN average, those without MetS were overweight, and those with MetS were obese (p<0.05). Among the latter, comparison of BMI at the time of cancer diagnosis and current BMI (27.8±5.4 versus 33.4±5.4 kg/m2) showed a significant weight gain (p<0.05). Mean CRP values were higher in women with MetS (p<0.05). In the comparison of tumor characteristics and cancer treatments there was no difference between groups (p>0.05). CONCLUSION: Postmenopausal breast cancer survivors had a higher risk of developing metabolic syndrome and central obesity.
Metabolic syndrome in postmenopausal breast cancer survivors
Keywords: Etiology metabolic syndrome X risk factors obesity; Menopause; Metabolism breast neoplasms